2022
DOI: 10.3390/coatings13010069
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Coatings on Implant Materials—A Systematic Review of the Current Scenario

Abstract: The challenges and demands of implant materials are changing as a result of the substantial expansion in the global population. Suitable implants are required for aged people, physical injuries, patients who need revised surgeries, contaminated implants, and accident victims. Hence, the requirement for implants is drastically increasing day by day. Metals, ceramics, and polymers are used as implant materials by biomedical industries for long-term suffering patients. Stainless steel, titanium and its alloys, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 86 publications
0
21
0
Order By: Relevance
“…[45,55,56] The investigations demonstrated that MAO-produced and Sr-P coatings have high degradation resistance, while CaP coatings can improve wear resistance. [57] Microstructural evolutions can also lead to significant changes in Mg-based biomaterials, for or hydroxyapatite (HA) [163,168] Tissue engineering scaffolds Mg-based coatings with controlled degradation rate and osteogenic ability Fluorohydroxyapatite (FHA) coating on magnesium alloys [163,171] Drug delivery systems Mg-based coatings with pH-responsive and sustained-release properties Degradable polymer coatings, silk fibroin coatings, and hierarchical hybrid coatings [163,167,172] www.advancedsciencenews.com www.aem-journal.com example, grain refinement by utilization of equal channel angular pressing or other variants of severe plastic deformation methods may enhance both the mechanical properties and degradation rate; this can lead to the fabrication of denser and thicker coating layers with improved corrosion resistance. [12,[58][59][60][61][62] In addition to the usual previous methods, new techniques and procedures have been proposed, invented, and studied for the better development of multifunctional coatings, such as plasma-induced thermal-field-assisted crosslinking deposition (PTCD) that is an environment-friendly method, enabling the fabrication of hierarchical textures with potential for the simultaneous growth of the inorganic layer and organic layer.…”
Section: Introductionmentioning
confidence: 99%
“…[45,55,56] The investigations demonstrated that MAO-produced and Sr-P coatings have high degradation resistance, while CaP coatings can improve wear resistance. [57] Microstructural evolutions can also lead to significant changes in Mg-based biomaterials, for or hydroxyapatite (HA) [163,168] Tissue engineering scaffolds Mg-based coatings with controlled degradation rate and osteogenic ability Fluorohydroxyapatite (FHA) coating on magnesium alloys [163,171] Drug delivery systems Mg-based coatings with pH-responsive and sustained-release properties Degradable polymer coatings, silk fibroin coatings, and hierarchical hybrid coatings [163,167,172] www.advancedsciencenews.com www.aem-journal.com example, grain refinement by utilization of equal channel angular pressing or other variants of severe plastic deformation methods may enhance both the mechanical properties and degradation rate; this can lead to the fabrication of denser and thicker coating layers with improved corrosion resistance. [12,[58][59][60][61][62] In addition to the usual previous methods, new techniques and procedures have been proposed, invented, and studied for the better development of multifunctional coatings, such as plasma-induced thermal-field-assisted crosslinking deposition (PTCD) that is an environment-friendly method, enabling the fabrication of hierarchical textures with potential for the simultaneous growth of the inorganic layer and organic layer.…”
Section: Introductionmentioning
confidence: 99%
“…They offer restorative solutions that would have otherwise been impossible [2]. With the fast evolution of all medical fields and the rise of the digital era, there is a continuous need for better, faster, and easier treatment modalities [3]. The modern dental implant has received countless upgrades and enhancements in almost every aspect when compared to its original predecessor [4].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, and in order to improve osseointegration and reduce healing time, Titanium implants with a nanostructured calcium-incorporated surface have been introduced [ 23 , 25 ]. In a systematic review of implant coatings, it was determined that the proper materials and preparation techniques are quintessential in implant success and play a major role in enhancing its durability and longevity [ 26 ]. In another systematic review, bioactive modifications of dental implant surfaces such as calcium-phosphate coating seemed to be more beneficial for osseointegration and early peri-implant bone formation when compared to SLA or similar surfaces [ 27 ].…”
Section: Introductionmentioning
confidence: 99%